1994
DOI: 10.1038/367480a0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nuclear hormone receptor activity by calreticulin

Abstract: We have shown that a polypeptide of M(r) 60,000 (60K) that shares N-terminal homology with a calcium-binding protein, calreticulin, can bind to an amino-acid sequence motif, KXGFFKR, found in the cytoplasmic domains of all integrin alpha-subunits. The homologous amino-acid sequence, KXFFKR (where X is either G, A or V), is also present in the DNA-binding domain of all known members of the steroid hormone receptor family; amino acids in this sequence make direct contact with nucleotides in their DNA-responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
235
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 349 publications
(245 citation statements)
references
References 23 publications
9
235
1
Order By: Relevance
“…Smith, 1988. b Hoffman et al, 1987Lasek et al, 1983. c Smith andKoch, 1989;Opas et al, 1991;Burns et al, 1994;Dedhar et al, 1994. d Brunet et al, 1991.…”
Section: Resultsmentioning
confidence: 99%
“…Smith, 1988. b Hoffman et al, 1987Lasek et al, 1983. c Smith andKoch, 1989;Opas et al, 1991;Burns et al, 1994;Dedhar et al, 1994. d Brunet et al, 1991.…”
Section: Resultsmentioning
confidence: 99%
“…It has three distinct domains: the amino terminal N-domain, the proline-rich P-domain, and the carboxyl-terminal C-domain (16 -18). The N-domain binds to the protein sequence KxFF[K/R]R, which is found in the cytoplasmic domain of the ␣-subunit of integrins (19) and in several steroid hormone receptors, including the glucocorticoid receptor (20), the androgen receptor, and the retinoic acid receptor (21). Perforin contains the amino acid sequence KVFF (residues 439 -442), which represents part of this calreticulin-binding motif.…”
Section: Perforin Lytic Activity Is Controlled By Calreticulinmentioning
confidence: 99%
“…It was first described as a calcium-binding protein of the sarcoplasmic reticulum of smooth-muscle cells [40,41]. Calreticulin has subsequently been shown (i) to possess a calcium-binding function [42] and chaperone activity [43] in the endoplasmic reticulum ; (ii) to have RNA binding activity [44] ; and (iii) to modify gene expression by binding to nuclear-hormone receptors [45,46]. It has also been shown that calreticulin can bind to the KXGFFKR motif within the α subunits of integrins [27] (where X indicates any residue), and that antisense oligonucleotide-mediated downregulation of calreticulin expression inhibits integrin-mediated adhesion of PC-3 and Jurkat cells [29].…”
Section: Discussionmentioning
confidence: 99%